Fundamentos da circulação de saberes nos espaços religiosos de matriz africana: análise no Ilê Alaketu Asè Omô Logunédè - Santos, Ademir Barros (Universidade Federal de São Carlos, 2018)
From a pedagogical and anthropological perspective, this research sought to identify the foundations present in the circulation, diffusion, apprehension and perpetuation of knowledge in environments linked to the religious matrix of African origin, understanding, as circulation, the transference and apprehension of the ritual knowledge and practices inherent in that belief system. The theme of study is the Ketu nation candomblé, particularly the Ilê Alaketu Asè Omô Logunédè Cult House, in which complex rituals continue to be learned and apprehended, perpetuated and transmitted, notwithstanding the absence of the traditional figure of the master or a written culture, as well as continually facing the harsh repudiation of Western Judeo-Christian societies, exacerbated along the historical slave trade process. The methodology used was qualitative and included bibliographical analysis, data collection in the field and participant observation. Theoretically, it relied on renowned names such as Kabengele Munanga, Amadou Hampâté Bâ, Roger Bastide and Pierre Verger, as well as on research related to the subject, such as “Educação nos Terreiros" (not avaiable in English), developed by Stella Guedes Caputo and "Convivendo com os Orixás" (not published) by Karla Geyb da Silva Queiroz; also in speeches such as that of Maria Stella de Azevedo Santos, Mother Stella de Oxossi, delivered in 2013, when she took office at the Bahia Academy of Letters, as well as a survey of the formation and history of candomblé in Brazil. Among the results achieved, it was observed that the adherence between the African cultural values and the practices of knowledge transmission in the diaspora happens in a very effective way, characterized by the respect to the longevity, communal dependency, circularity, playfulness, notion of a necessary complementarity among all the individuals, as well as other elements that are part of the processes studied. Thus, this dissertation aims to collaborate with the production of knowledge in the field of fundamentals of educational processes of non-school education.

RESUMEN De sesgo pedagógico-antropológico, esta investigación buscó identificar los fundamentos presentes en la circulación, difusión, aprehensión y perpetuación de saberes en ambientes vinculados a la matriz religiosa de origen africana, entendiendo “circulación” como la transferencia y aprehensión de los saberes y haceres rituales inherentes a esta creencia. El tema de estudio es el candomblé de nación Ketu, en particular la Casa de Culto Ilê Alaketu Asè Omô Logunédè, en la que rituales complejos aún son aprendidos y aprehendidos, perpetuados y transmitidos, aunque prescindiendo de la figura tradicional del maestro y de la escritura, así como continuamente enfrentando el acentuado repudio de las sociedades judeocristianas occidentales, exacerbado en el largo proceso esclavista. La metodología empleada fue la cualitativa y contó con análisis bibliográfico, relevamiento de datos en el campo e investigación participante. En térmimos teóricos, se fundamentó en nombres consagrados como, entre otros, Kabengele Munanga, Amadou Hampâté Bâ, Roger Bastide e Pierre Verger, además de investigaciones producidas sobre el tema, como la "Educação nos terreiros" (no disponible en espanõl), desarrollada por Stela Guedes Caputo y “Convivendo com os orixás”, de Karla Geyb da Silva Queiroz (no publicado); también en discursos como el de Maria Stella de Azevedo Santos, llamada Mãe Estela de Oxossi, proferido en el 2013, durante su nombramiento en la Academia de Letras de Bahía, además del relevamiento de la formación y la historia del candomblé en Brasil. Entre los resultados alcanzados, se constató que la adherencia entre los valores culturales africanos y las prácticas de transmisión de saberes en la diáspora ocurre de forma bastante eficaz, caracterizada por el respeto a la longevidad, la dependencia comunal, la circularidad, la ludicidad y la noción de complementariedad necesaria entre todos los individuos, además de otros elementos integrantes de los procesos estudiados. Así, la presente disertación quiere colaborar con la producción del conocimiento en el campo de los fundamentos de procesos educativos de la educación no escolar.
Fundamentals of the circulation of knowledge in the African matrix religious spaces: analysis in the ilê Alaketu Asè Omô Logunédè
Keywords: Casa de Culto Ilê Alaketu Asè Omô Logunédè; House of worship Ilê Alaketu Asè Omô Logunédè; Candomblé; Educação não escolar; Educação e relações étnico-raciais; Religiões de matriz africana; Non-school education; Education and ethnic-racial relations; Religions of African Matrix.; Educación no escolar; Educación y relaciones étnico-raciales; Religiones de matriz Africana; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO